2019
DOI: 10.1371/journal.ppat.1007658
|View full text |Cite
|
Sign up to set email alerts
|

Subversion of natural killer cell responses by a cytomegalovirus-encoded soluble CD48 decoy receptor

Abstract: Throughout evolution, cytomegaloviruses (CMVs) have been capturing genes from their hosts, employing the derived proteins to evade host immune defenses. We have recently reported the presence of a number of CD48 homologs (vCD48s) encoded by different pathogenic viruses, including several CMVs. However, their properties and biological relevance remain as yet unexplored. CD48, a cosignaling molecule expressed on the surface of most hematopoietic cells, modulates the function of natural kil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 56 publications
1
26
0
Order By: Relevance
“…Can be blocked via interactions with CMV SLAMF2 decoy receptor [43] Influenza viral HA protein [44] T cell exhaustion [45][46][47][48][49][50] NK cells, CD8 + T cells, NKT cells, γδ T cells, monocytes, basophils, eosinophils, DCs, mast cells SLAMF5 (CD84) DC pro-inflammatory signaling [19] Germinal center formation [33] B cells, T cells, monocytes, macrophages, DCs, platelets, thymocytes, NK cells, NKT cells, basophils, eosinophils.…”
Section: Slamf4 (2b4 Cd244)mentioning
confidence: 99%
See 3 more Smart Citations
“…Can be blocked via interactions with CMV SLAMF2 decoy receptor [43] Influenza viral HA protein [44] T cell exhaustion [45][46][47][48][49][50] NK cells, CD8 + T cells, NKT cells, γδ T cells, monocytes, basophils, eosinophils, DCs, mast cells SLAMF5 (CD84) DC pro-inflammatory signaling [19] Germinal center formation [33] B cells, T cells, monocytes, macrophages, DCs, platelets, thymocytes, NK cells, NKT cells, basophils, eosinophils.…”
Section: Slamf4 (2b4 Cd244)mentioning
confidence: 99%
“…Due to SLAMF2's importance in regulating CMI, it was theorized that some viruses may attempt to modulate SLAMF2 to circumvent its role in combating viral infections. Indeed, it was found that cytomegalovirus (CMV), HIV, and potentially, human T cell leukemia virus type 1 (HTLV-1), have evolved to do just this [41,43,57,58]. CMV is able to evade SLAMF2-mediated immune responses via two independent mechanisms: down-regulation of SLAMF2 on infected cells via the viral protein m154 [41] and by producing a soluble SLAMF2 decoy receptor [43].…”
Section: Slamf2 (Cd48)mentioning
confidence: 99%
See 2 more Smart Citations
“…Some plant viruses increase the plant survival by preventing the induction of stress caused by cold and drought . Throughout evolution, some viruses such as Herpesviridae family have been capturing genes from their hosts that leads to evade recognition by host immune system and remain latent in host cells . Therefore, the ability to launch latent infection is a particular feature of Herpesviridae family such as cytomegalovirus (CMV)…”
Section: Two‐sided Communication Between the Virus And The Host (Mutumentioning
confidence: 99%